Upaya Mengurangi Waste Produksi Root Blower di PT. Intidaya Dinamika Sejati Jember - Aurellia Verren Krestandio; Prayonne Adi (Jurnal Titra, 2022)
PT. Intidaya Dinamika Sejati is a company engaged in design, engineering and service in the industrial and general business sectors in Indonesia. The services offered are for various products such as vacuum pumps, air-end compressors, control panels, roots blowers, and air locks. The two main products produced at PT. Intidaya Dinamika Sejati, namely the medical system and root blower. Waste is any form of activity that does not add value to the product (Ridwan et al. [1]). The results of observations and interviews with companies show that waste of time and energy caused by several factors occurs at PT. Intidaya Dinamika Sejati. Observations were made to obtain cycle time, value stream mapping and waste analysis. The results of the analysis show that there is waste waiting, motion, transportation and defects. Waste analysis is carried out with the help of the value stream mapping tool. Proposals are given to reduce the waste that occurs. The proposal is expected to reduce defects, unnecessary movement of workers and waiting time.